Short-Term Efficacy and Safety of Pazopanib Combined with Chemotherapy in Treatment of Advanced Synovial Sarcoma - Jing WANG; Feng LIN (Zhongliu Fangzhi Yanjiu)
ObjectiveTo investigate the short-term efficacy and safety of pazopanib combined with chemotherapy in the treatment of advanced synovial sarcoma (SS). MethodsA total of 64 patients with advanced SS treated with pazopanib combined with different chemotherapy regimens were selected. Among them, 26 patients received first-line chemotherapy regimen, 19 patients received second-line chemotherapy regimen, and 19 patients received third-line chemotherapy regimen. The therapeutic efficacy and safety of different treatment regimens were evaluated. ResultsOut of the 64 patients, 33 achieved partial response (PR), 12 had stable disease (SD), and 19 experienced progression disease (PD). The objective response rate (ORR) and disease control rate (DCR) were 51.6% (33/64) and 70.3% (45/64), respectively, with a median progression-free survival (PFS) of 7.55 months (95%CI: 6.320–8.780 months). Among the 26 patients treated with the first-line chemotherapy regimen, the ORR was 65.4% (17/26), the DCR was 73.1% (19/26), and the median PFS was 9.167 months (95%CI: 6.362–11.971 months). For the 19 patients receiving second-line chemotherapy regimen, the ORR was 47.4% (9/19), the DCR was 73.7% (14/19), and the median PFS was 7.55 months (95%CI: 6.054–9.046 months). Among the 19 patients treated with the third-line chemotherapy regimen, the ORR was 36.8% (7/19), the DCR was 63.2% (12/19), and the median PFS was 6.09 months (95%CI: 3.158–9.022 months). The majority of adverse events were grade Ⅰ/Ⅱ, whereas grade Ⅲ/Ⅳ adverse events rarely occurred. No deaths occurred during the course of treatment. ConclusionPazopanib combined with chemotherapy shows good efficacy in the treatment of advanced SS, with acceptable adverse events.